Marketing Staff: Individual Development through Strategies and Planning (Research, Society and Development, 2019)
Marketing is of great importance to all segments. It is no different for the individual, where he or she needs to be prepared to meet the demands imposed by the market, and then seek to improve their skills, knowledge and skills, seeking alternatives and professional qualification, developing some specific skills and seeking the maximum excellence in your personal marketing. This research aims to highlight the strategic tools used by personal marketing and the importance of these practices in personal and professional development, based on a bibliographical study and a theoretical framework based on the authors who study the theme. It has been verified that personal and professional marketing is being increasingly used, both by people who are starting their career and also those who intend to grow within the company, mainly due to the requirements of the market. From the studies carried out it is possible to perceive that although it is being a tool, it is increasingly used, although there are still several tools that are not exploited as they should.